Understanding of Final Year Medical, Pharmacy and Nursing Students in Pakistan towards Antibiotic Use, Antimicrobial Resistance and Stewardship: Findings and Implications - Iqra Raees; Hafiz Muhammad Atif; Sabahat Aslam; Zia Ul Mustafa; Johanna Catharina Meyer; Khezar Hayat; Muhammad Salman; Brian Godman (MDPI AG, 2023)
Antimicrobial resistance (AMR) is a leading public health threat, which is exacerbated by the high and inappropriate use of antibiotics. Consequently, there is a need to evaluate knowledge regarding antibiotic use, AMR and the readiness to implement antimicrobial stewardship programs (ASPs) among final year medical, pharmacy and nursing students in Pakistan. This reflects the high and increasing rates of AMR in the country, and students as future healthcare professionals (HCPs). A cross-sectional study was conducted among 1251 final year students from 23 public and private educational institutions in Punjab. The majority of the surveyed participants possessed good knowledge of antibiotic use, AMR and the potential causes of AMR. The most common sources of the information on antibiotics were smartphones (69.9%), peers (35.9%) and medical textbooks (30.6%). However, most surveyed participants were not fully prepared to participate in ASPs. They knew, though, how to reduce AMR by educating HCPs about appropriate prescribing, implementing ASPs and improving laboratory facilities. There was a significant association between antibiotic knowledge and causes of AMR with sex, family income and student type (p < 0.05). Being a student at a public sector university (OR = 4.809; CI = 3.261-7.094; p < 0.001) and age (OR = 0.524, CI = 0.327-0.842; p < 0.008) were among the key factors impacting students' training on ASPs. Educational curricula must be improved to include more information about appropriate antibiotic use and ASPs, along with sufficient training, workshops and clinical rotations in the final year, to fully equip students by graduation.